Collapsin Response Mediator Protein 2 (CRMP2) Interacts with N-Methyl-d-aspartate (NMDA) Receptor and Na(+)/Ca(2+) Exchanger and Regulates Their Functional Activity - Brustovetsky, Tatiana (American Society for Biochemistry and Molecular Biology, 2014)
Collapsin response mediator protein 2 (CRMP2) is traditionally viewed as an axonal growth protein involved in axon/dendrite specification. Here, we describe novel functions of CRMP2. A 15-amino acid peptide from CRMP2, fused to the TAT cell-penetrating motif of the HIV-1 protein, TAT-CBD3, but not CBD3 without TAT, attenuated N-methyl-d-aspartate receptor (NMDAR) activity and protected neurons against glutamate-induced Ca(2+) dysregulation, suggesting the key contribution of CRMP2 in these processes. In addition, TAT-CBD3, but not CBD3 without TAT or TAT-scramble peptide, inhibited increases in cytosolic Ca(2+) mediated by the plasmalemmal Na(+)/Ca(2+) exchanger (NCX) operating in the reverse mode. Co-immunoprecipitation experiments revealed an interaction between CRMP2 and NMDAR as well as NCX3 but not NCX1. TAT-CBD3 disrupted CRMP2-NMDAR interaction without change in NMDAR localization. In contrast, TAT-CBD3 augmented the CRMP2-NCX3 co-immunoprecipitation, indicating increased interaction or stabilization of a complex between these proteins. Immunostaining with an anti-NCX3 antibody revealed that TAT-CBD3 induced NCX3 internalization, suggesting that both reverse and forward modes of NCX might be affected. Indeed, the forward mode of NCX, evaluated in experiments with ionomycin-induced Ca(2+) influx into neurons, was strongly suppressed by TAT-CBD3. Knockdown of CRMP2 with short interfering RNA (siRNA) prevented NCX3 internalization in response to TAT-CBD3 exposure. Moreover, CRMP2 down-regulation strongly attenuated TAT-CBD3-induced inhibition of reverse NCX. Overall, our results demonstrate that CRMP2 interacts with NCX and NMDAR and that TAT-CBD3 protects against glutamate-induced Ca(2+) dysregulation most likely via suppression of both NMDAR and NCX activities. Our results further clarify the mechanism of action of TAT-CBD3 and identify a novel regulatory checkpoint for NMDAR and NCX function based on CRMP2 interaction with these proteins.